KORELASI ANTARA PENAYANGAN INDONESIAN IDOL SEASON SEPULUH DI RCTI DENGAN MINAT MENONTON MASYARAKAT DI DESA BATUKARANG - Waris Ginting; Liasta Ras Menda Sebayang (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2020)
This study aims at determining the correlation between the broadcast of Indonesian Idol Season Ten on RCTI and the interest in watching the community in Batukarang Village. A quantitative descriptive approach is used in this research. Data collection techniques are using observation and in-depth interviews with research informants and using literature or documents that support the research. From the research results, it can be concluded that the effect of the Indonesian Idol program's exposure to the interest in watching the people of Batukarang Village, Payung District, Karo Regency is 27.04%. These results are supported by the results of hypothesis testing using the product moment correlation formula which obtains rcount of 0.52 or is in the poor correlation category (0.41 - 0.70). To see the exposure of the Indonesian Idol program, the authors in this study describe it into 3 (three) indicators, namely program concept, frequency of use and duration of use. The results of the research data collection were obtained, the exposure of the Indonesian Idol program among the people of Batukarang Village, Payung District, Karo Regency amounting to 51.20% which is interpreted from a total score of 1715 points. The people's penchant for watching programs that are becoming trendsetters can also be a factor in obtaining this value.